Kedisiplinan Siswa Dalam Pembelajaran PAI Di SMPN 1 Rao Selatan Kabupaten Pasaman - Noormaya Dwita Sari; Darul Ilmi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The background of this writing is because there are several problems that occur related to student discipline in learning PAI at SMP N 1 Rao Selatan, Pasaman Regency. Among them is that there are still students who are not paying attention when the teacher is teaching, then students are less disciplined in timeliness when learning PAI and students are less responsible for the assignments given by the teacher. The researcher aims to find out how student discipline is in learning PAI at SMP N 1 Rao Selatan, Pasaman Regency and what are the constraints and supports for student discipline in learning PAI at SMP N 1 Rao Selatan. This research uses a qualitative descriptive research approach. While the data collection techniques that the authors use are observation, interviews and documentation. The key informants in this study were students of SMP N 1 Rao Selatan and Islamic Religious Education teachers as supporting informants. The results of this study prove that student discipline in learning PAI at SMP N 1 Rao Selatan, Pasaman Regency, namely first, students lack discipline in the learning process. This can be seen from the students' lack of attention when the teacher is explaining the lesson, then the students still like to talk and even sleep when the teacher explains the lesson. Then there are still students late for class when PAI learning has started, and there are still students who are negligent about the assignments given by the PAI teacher, for example students are lazy to do assignments and there are still students who are not independent in doing assignments. Second, Student Discipline Constraints in learning PAI, namely students' self-awareness that lacks the importance of discipline and students feel burdened by memorizing a lot of verses. The three factors supporting student discipline in learning PAI are mainly from student self-awareness, then the family environment must also provide encouragement and help children get used to being disciplined for example getting children to be disciplined at home, apart from that the school environment and community also contribute to supporting attitudes. child discipline, namely by continuing to monitor and try to implement disciplinary rules together.